Modulatory effects of selenium and zinc on the immune system - Ferencík, M; Ebringer, L (Folia microbiologica, 2003)
Almost all nutrients in the diet play a crucial role in maintaining an "optimal" immune response, and both insufficient and excessive intakes can have negative consequences on the immune status and susceptibility to a variety of pathogens. We summarize the evidence for the importance of two micronutrients, selenium and zinc, and describe the mechanisms through which they affect the immune status and other physiological functions. As a constituent of selenoproteins, selenium is needed for the proper functioning of neutrophils, macrophages, NK cells, T lymphocytes and some other immune mechanisms. Elevated selenium intake may be associated with reduced cancer risk and may alleviate other pathological conditions including oxidative stress and inflammation. Selenium appears to be a key nutrient in counteracting the development of virulence and inhibiting HIV progression to AIDS. It is required for sperm motility and may reduce the risk of miscarriage. Selenium deficiency has been linked to adverse mood states and some findings suggest that selenium deficiency may be a risk factor in cardiovascular diseases. Zinc is required as a catalytic, structural and regulatory ion for enzymes, proteins and transcription factors, and is thus a key trace element in many homeostatic mechanisms of the body, including immune responses. Low zinc ion bioavailability results in limited immunoresistance to infection in aging. Physiological supplementation of zinc for 1-2 months restores immune responses, reduces the incidence of infections and prolongs survival. However, in every single individual zinc supplementation of food should be adjusted to the particular zinc status in views of the great variability in habitat conditions, health status and dietary requirements.
Keywords: selen; Immune System; Selenium; potravní doplňky; imunitní systém; zinek; mužské pohlaví; ženské pohlaví; Zinc; Humans; Female; Dietary Supplements; lidé; Male